QUALITY DEVELOPMENT OF ACADEMIC SERVICES UNIT MANAGEMENT OF MACHULALONGKORNRAJAVIDAYALAYA UNIVERSITY: Sukusar Nuntong - นุ่นทอง สุขอุษา (Journal of MCU Social Science Review, 2018)
Objectives of this research were to: 1. Study general status of Off-Campus learning center administration of Mahachulalongkornrajavithayalaya University, 2. Study factors related to the administrative quality development of Off-Campus learning centers of Mahachulalongkornrajavithayalaya University and 3. Propose the guidelines for the administrative quality development of Off-Campus learning centers of Mahachulalongkornrajavithayalaya University Methodology was the mixed methods. The quantitative research collected data by questionnaires with reliability value at 0.931 from 103 samples, by stratified sampling, who were administrators, lecturers and personnel at Off-Campus learning centers and analyzed data by frequency, percentile, mean, standard deviation and Pearson’s Correlation Coefficient. The qualitative research collected data from 18 key informants with in-depth-interviewing and 10 participants in focus group discussion and analyzed data by descriptive interpretation. The result of the research found that 1. Status of Off-Campus learning center administration of Mahachulalongkornrajavithayalaya University in 5 areas were at middle level ( =3.30). Administration of each areas were that; personnel, financial and academic administration were at high level. The general and research administration were at middle level. 2. Factors related to Off-Campus learning center administration of Mahachulalongkornrajavithayalaya University were at low level ( =0.284) with significant value at 0.01. The application of Itthipada 4 for the Off-Campus learning center administration of Mahachulalongkornrajavithayalaya University had positive correlation at the middle level ( =0.539) with significant value at 0.01, accepting the hypothesis. 3. The guidelines for Off-Campus learning center administration of Mahachulalongkornrajavithayalaya University consisted of 5 aspects; 1) general administration according to Buddhadhamma, guideline for development was to encourage personnel to love and put efforts and intention into administration and use instinct to scrutinize the cause and effects of general administration, 2) academic administration according to Buddhadhamma, guideline for development was to train personnel to understand the academic works set forwards in advance, follow the set plans to meet the target, encourage personnel to set strong determination to academic works and use wisdom to solve any problems and improvement, 3) research administration according Buddhadhamma, the guideline for development was encourage personnel to love, to put efforts, to sacrifice the time and to use wisdom to research administration, 4) financial administration according to Buddhadhamma, the guideline for development was encourage personnel to love and to satisfy with the financial administration, to encourage personnel to put efforts into financial administration to prevent the risk, to use wisdom for examining the cause and effects of the financial administration for the good cause and 5) personnel administration according to Buddhadhamma, the guideline for development was to build team continuously at least for 5 years, encourage personnel to satisfy, sacrifice the time to the personnel administration, to continuously check and evaluate the work for effective improvement and development.